Representasi Pengetahuan Sistem Pakar Menggunakan Struktur Data Redis - Sammir, Haddad; Hamdi, Khairil; Sunaryo, Budi (Prosiding SISFOTEK, 2024)
This research discusses knowledge representation in expert systems using the Redis data structure, with a focus on the knowledge-based inference process. Inference in an expert system involves comparing existing facts with an existing database. When the elements in the rule match the database, the rule is considered TRUE and processed further in the database. For efficiency and speed in the inference process, this research utilizes the Redis data structure, especially the "sets" data structure type, which allows set operations to be carried out quickly and effectively. This research also suggests a convention for writing keys and values in Redis so that data consistency and integrity is maintained. Through this implementation, it is hoped that the expert system can process and make decisions more efficiently, utilizing Redis' advantages in set-based data management and access.